Intragastric balloon treatment of obesity: Long-term results and patient satisfaction - El Haddad, Aline; O. Rammal, Mohammad; Soweid, Assaad; I. Sharara, Ala; Daniel, Fady; A. Rahal, Mahmoud; Shaib, Yasser (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Intragastric balloon (IGB) treatment of obesity is a minimally invasive outpatient procedure that has been shown to help weight loss in some patients. The aim of this study is to analyze the long-term results regarding the effectiveness, tolerability, and patient satisfaction in a cohort of patients undergoing the IGB insertion. Materials and Methods: Using a retrospective cohort study design, patients who had their IGB inserted/removed between the years 2009 and 2016 were contacted by phone and asked to answer a short questionnaire. The baseline characteristics, pre- and post- IGB weight, as well as their current weight were recorded. Different parameters of satisfaction were noted in addition to whether patients resorted to alternative weight-reduction measures. Results: Ninety-nine eligible patients were contacted, and 65 consented to the study. The average weight loss achieved at the end of the treatment period (3 to 10 months) was approximately a 12% decrease from the baseline. Only 39% of patients were satisfied with the procedure, and less than 50% were satisfied with the weight loss achieved. When assessing the long-term follow-up, years after the IGB removal (3.3±1.76 years), the vast majority of patients (78.7%) regained weight or resorted to further bariatric measures. Conclusion: IGB leads to weight loss among most patients, but it does not appear to fulfill patients’ expectations. Further, the initial weight loss is not sustainable over time. Cite this article as: El Haddad A, Rammal MO, Soweid A, et al. Intragastric balloon treatment of obesity: Long-term results and patient satisfaction. Turk J Gastroenterol 2019; 30(5): 461-6.